Advancing Our Understanding of Psychological Stress and Coping Among Parents in Organized Youth Sport - Harwood, Chris G.; Thrower, Sam N.; Slater, Matthew J.; Didymus, Faye F.; Frearson, Lucy (Frontiers in Psychology, 2019)
The current study investigated psychological stress among parents of competitive British tennis players. Adopting a multipart concurrent mixed method design, 135 British tennis parents completed a cross sectional online questionnaire to examine their primary appraisals, emotions, and coping strategies associated with self-disclosed stressors. Hierarchical content analysis was conducted on open ended questionnaire responses to identify key stressors and coping strategies, and descriptive and inferential statistics were utilized to explore the differences between various components of the process. The findings revealed a range of organizational, competitive, and developmental stressors. These stressors were predominantly appraised as harm or challenge, and anxiety and anger were the most prominent emotions that the parents experienced. Statistically, parents experienced greater anger in relation to competition (compared to organizational and developmental) stressors, whilst harm appraisal increased negative emotions, and challenge appraisal increased positive emotions. Findings also highlighted how parents used a number of mastery, internal regulation, and goal withdrawal coping strategies, which varied statistically in degrees of reported effectiveness. The contribution of these findings to the stress literature and their applied implications are discussed. Keywords: sport parents, stressors, appraisal, emotion, coping, coping effectiveness, mixed method.